2020
DOI: 10.1016/j.apgeog.2019.102126
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of various street-level characteristics on the burden of urban burglary in Kaduna, Nigeria

Abstract: Evidence suggests that crimes committed in urban environments are geographically concentrated across a range of scales, and that the variation in rates of crime within an urban space is significantly dependent on the physical environment as well as the situation in which the crime takes place. However, these assertions are typically drawn from environmental criminological studies that have focussed on Euro-American cities and western intellectual perspectives. We seek to move beyond these by focussing on a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One type of crime that has significant ramifications is burglary, which involves unlawful entry into a building or structure with the intent to commit theft or another felony (Brantingham and Brantingham, 1995;Eck and Eck, 2003). Burglary is a major concern for individuals, researchers, law enforcement agencies, and policymakers, particularly in developing countries such as Nigeria, where it is a pervasive problem with high rates reported in urban and suburban areas (Musah et al, 2020;Iliyasu et al, 2022;Alabi and Abubakar, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One type of crime that has significant ramifications is burglary, which involves unlawful entry into a building or structure with the intent to commit theft or another felony (Brantingham and Brantingham, 1995;Eck and Eck, 2003). Burglary is a major concern for individuals, researchers, law enforcement agencies, and policymakers, particularly in developing countries such as Nigeria, where it is a pervasive problem with high rates reported in urban and suburban areas (Musah et al, 2020;Iliyasu et al, 2022;Alabi and Abubakar, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In geographic criminology, it is increasingly recognized that the appropriate spatial unit of analysis needs to be considered explicitly and carefully chosen [15]. At different spatial scales, crime concentration (specifically, burglary and family theft) differs [16]. Researchers have found that crimes are more concentrated when smaller geographic units were used for analysis, and recent research has focused on addresses [17,18], street segments [19][20][21][22], and houses [23,24].…”
Section: Introductionmentioning
confidence: 99%